Structural changes in cerebral arteries following nitric oxide deprivation: a comparison between normotensive and hypertensive rats - Hsieh, Nan K.; Wang, Jia Y.; Liu, Jiang C.; Lee, Wei H.; Chen, Hsing I. (Thrombosis and Haemostasis, 2004)
Chronic inhibition of nitric oxide (NO) synthesis with Nωnitro-L-arginine methyl ester (L-NAME) has become a model of hypertension. The purpose of this study was to evaluate the morphological changes of cerebral arteries in rats with genetic hypertension and hypertension induced by chronic NO deprivation. Spontaneously hypertensive rats (SHR) and normotensive Wistar-Kyoto strain (WKY) were given L-NAME (1 mg·ml-1) from age 5 to 7 or 9 weeks. We assessed vascular remodelling and arteriolar injury score (AIS) in various cerebral arteries using different immunohistochemical staining techniques. In WKY and SHR, L-NAME caused an elevation in tail cuff pressure (TCP). The increase in TCP was larger in SHR than in WKY. L-NAME decreased body weight, but increased heart weight in SHR.The lumen diameter and media cross-section area of internal carotid artery (ICA) in SHR were smaller than those in WKY, and further reduced in SHR and WKY after L-NAME treatment. These findings indicate that cerebral vascular remodelling occurs following chronic hypertension either from genetic origin or NO deprivation. L-NAME increased the media thickness in SHR, but not in WKY. This agent also caused an increase in cell volume density, AIS, and inflammatory cells infiltration in perivascular space with a negative growth index in ICA. The media/lumen ratio was higher in SHR than WKY, and further increased following L-NAME treatment. Diversified vascular remodelling occurred in hypertensive rats, but not in untreated WKY. In summary, these results suggest that NO deprivation and genetic hypertension cause vascular changes in various cerebral arteries.
Keywords: Hypertension; vascular remodelling; nitric oxide blockade; inflammatory cell; stroke